Heat and mass transfer phenomenon for the dynamics of Casson fluid through porous medium over shrinking wall subject to Lorentz force and heat source/sink - Awais, Muhammad; Raja, Muhammad Asif Zahoor; Awan, Saeed Ehsan; Shoaib, Muhammad; Ali, Hafiz Muhammad (Alexandria engineering journal, 2021)
The present investigation explores the impact of mass and heat transfer on the magneto-hydrodynamic (MHD) flow of Casson fluid through porous medium due to shrinking wall subject to Lorentz force and heat generation/absorption effects. Dual branches for the profiles of velocity, temperature and mass fraction have been computed numerically by exploitation of explicit Runge-Kutta procedure. Mathematical modelling is developed for the conversion of physical model into set of mathematical equations which are simplified using order analysis. The computations for the solution construction have been made numerically via shooting technique and the results are obtained for stream function, temperature and concentration profiles. The aim of presented analysis is to observed that the dual numerical solutions exist for stream functions, skin friction, temperature and concentration profiles. Graphical illustrations have been prepared for different physical quantities including transfer of mass, heat absorption/generation, influence of chemical reaction, Schmidt number and non-Newtonian parameter etc. Results of proposed method are also provided to describe the dual solutions for the local Nusselt and Sherwood numbers as well as for heat transfer rate for Propane and Ethelene Glycol. The Prandtl number and Schmidt number decay the temperature and concentration profiles, respectively.